A cyclin-dependent kinase, CDK11/p58, represses cap-dependent translation during mitosis - An, Sihyeon (Cell Mol Life Sci, 2020)
During mitosis, translation of most mRNAs is strongly repressed; none of the several explanatory hypotheses suggested can fully explain the molecular basis of this phenomenon. Here we report that cyclin-dependent CDK11/p58—a serine/threonine kinase abundantly expressed during M phase—represses overall translation by phosphorylating a subunit (eIF3F) of the translation factor eIF3 complex that is essential for translation initiation of most mRNAs. Ectopic expression of CDK11/p58 strongly repressed cap-dependent translation, and knockdown of CDK11/p58 nullified the translational repression during M phase. We identified the phosphorylation sites in eIF3F responsible for M phase-specific translational repression by CDK11/p58. Alanine substitutions of CDK11/p58 target sites in eIF3F nullified its effects on cell cycle-dependent translational regulation. The mechanism of translational regulation by the M phase-specific kinase, CDK11/p58, has deep evolutionary roots considering the conservation of CDK11 and its target sites on eIF3F from C. elegans to humans. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00018-019-03436-3) contains supplementary material, which is available to authorized users.